(untitled) (Olhar de Professor, 2021)
This article focuses on the materials that make up the productions of Art and the materials offered to children in school contexts. It is understood that currently in the field of Art any material is considered as a vehicle for configuring ideas and in schools the traditional materials endure. What are today’s Art materials? How does the School understand the materials of Art? These are the questions that guided reflections on the presence / absence of Art materials, as well as their uses in educational contexts. For this purpose, data from research developed at the undergraduate and graduate level of a Faculty of Education and research on social networks were used. It is understood that the transformations carried out in the field of Art since the middle of the century. XIX arrived slowly in children’s educational contexts, with a lack of understanding of the need to bring other materials for children to expand their research and creation processes.